Soil microbial community, enzyme activity, C and N stocks and soil aggregation as affected by land use and soil depth in a tropical climate region of Brazil - Sarto, Marcos V. M.; Borges, Wander L. B.; Bassegio, Doglas; Pires, Carlos A. B.; Rice, Charles W.; Rosolem, Ciro A. [UNESP] (Springer Nature, 2020)
The impact of agricultural land-use on soil microbial community composition and enzyme activity has not been extensively investigated in Ultisols. We investigated soil health parameters by analyzing phospholipid fatty acids (PLFAs), extracellular enzyme activity, C and N stocks, and soil structure. Four land uses were established in a tropical climate region of Brazil: native Cerrado (savanna), monoculture pasture [Urochloa brizantha (Hochst. Ex A. Rich.) R. Webster 'Marandu'], an integrated crop-livestock system (ICLS), and maize (Zea mays)-fallow in a no-tillage system. Soil microbial biomass was 40% higher in the native Cerrado than in the monoculture pasture, ICLS, and no-tillage maize. Soil organic carbon was positively correlated with microbial community composition (MB; gram–; AC; AMF; Fungi; F: B ratio) and enzyme activity (bG, AP, NAG). Large macroaggregates were positively correlated with bG, AP, and AMF. In summary, the native Cerrado had a higher level of carbon at the soil surface and greater soil structure with increased microbial biomass, gram+ bacteria, AMF, fungi, and F:B ratio in a tropical region of Brazil. However, bG and AP enzyme activities were lower in the ICLS and no-till maize at the soil surface (0–5 cm) compared to the native Cerrado. The conversion of native Cerrado to agricultural systems shifted the soil microbial community composition, enzyme activity, C and N, and soil structure of this sandy soil of the Brazilian Cerrado.
Keywords: Cerrado; No-tillage; Pasture; Phospholipid fatty acids (PLFAs); Soil health